PENGEMBANGAN WISATA HALAL OLEH PEMERINTAH SINGAPURA UNTUK MENARIK MINAT WISATAWAN INDONESIA - Safitri, Dian; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The Singapore Tourism Board (STB) is a legal entity under the Singapore Ministry of Trade and Industry. Development of Singapore's tourism sector, one of the service sectors and the country's main economic pillar, and conduct marketing and promotion of Singapore as a tourist destination. Singapore is stepping up its services to Muslim travelers with a major campaign to be launched. The purpose of the study is to explain and find out the development of halal tourism by the Singapore government to attract Indonesian Muslim tourists. The research method used is qualitative by connecting the causes and effects that occur using library research techniques. This study collects data through secondary data.The results of this study can be concluded that these places to eat get certification from MUIS (Majlis Ugama Islam Singapore). Tourists can easily visit Halal places to eat all over Singapore. In addition, there are also many mosques and prayer rooms throughout Singapore for visitors to worship while on vacation. This guide provides useful information for holidays in Singapore. The Singapore Tourism Board (STB) announced that it will be working with booking platform Have Halal Will Travel (HHWT) and research firm CrescentRating on a range of tourism products and marketing assurance targeting of Muslim Travelers across Asia.The STB with CrescentRating that details not only halal dining offerings in Singapore, but also the hidden cultural activities and local Malay entrepreneurs and business owners that tourists can discover, said Fazal Bahardeen, CEO of CrescentRating & Halaltrip.  Keywords: halal tourism, Singapore, Indonesian Muslim tourists